1996
DOI: 10.1007/bf01458181
|View full text |Cite
|
Sign up to set email alerts
|

Higher-level systematics of rodents (Mammalia, Rodentia): Evidence from the mitochondrial 12S rRNA gene

Abstract: Phylogenetic relationships among major rodent superfamilies traditionally have been difficult to establish because of the apparent high level of convergence and parallelism seen among morphological characters and/or rapid differentiation of rodent groups in the Paleocene/Eocene. Nucleotide sequence data from the mitochondrial 12S rRNA gene were used to clarify phylogenetic relationships among the major groups of rodents as defined by Brandt (1855) and Tullberg (1899). Based on the approximately 800 bp analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 108 publications
(188 reference statements)
2
47
1
1
Order By: Relevance
“…South American hystricognaths, greater in diversity than their African counterparts, evidently diversified rapidly after their arrival in the New World, contributing to the obscure phylogenetic relationships among the group's major clades, which have been traditionally accorded family or superfamily rank. Moreover, a high degree of parallelism appears to have marked the morphological (Hartenberger, 1985) and molecular (Nedbal et al, 1996) evolution of caviomorphs, further complicating our understanding of their higher-level interrelationships. The phylogenetic placement of many modern and extinct forms thus continue to be debated, sometimes even at high taxonomic levels (Cabrera, 1961;Anderson and Jones, 1984;Corbet and Hills, 1991;Wilson and Reeder, 1993;McKenna and Bell, 1998;Woods and Kilpatrick, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…South American hystricognaths, greater in diversity than their African counterparts, evidently diversified rapidly after their arrival in the New World, contributing to the obscure phylogenetic relationships among the group's major clades, which have been traditionally accorded family or superfamily rank. Moreover, a high degree of parallelism appears to have marked the morphological (Hartenberger, 1985) and molecular (Nedbal et al, 1996) evolution of caviomorphs, further complicating our understanding of their higher-level interrelationships. The phylogenetic placement of many modern and extinct forms thus continue to be debated, sometimes even at high taxonomic levels (Cabrera, 1961;Anderson and Jones, 1984;Corbet and Hills, 1991;Wilson and Reeder, 1993;McKenna and Bell, 1998;Woods and Kilpatrick, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for some molecular markers, rodents have been shown to display extensive lineage-specific substitution rate heterogeneities in nuclear genes (Huchon et al 2000;Adkins et al 2001), even between closely related taxa (e.g., Fieldhouse et al 1997;Michaux and Catzeflis 2000;Michaux et al 2001;Rowe and Honeycutt 2002). Additionally, several molecular studies, based on both mitochondrial and nuclear genes, have provided a reasonably good picture of phylogenetic relationships of rodents and other placentals (Nedbal et al 1994(Nedbal et al , 1996Catzeflis et al 1995;Huchon et al 1999Huchon et al , 2000Huchon et al , 2002Adkins et al 2001;Huchon and Douzery 2001;DeBry and Sagel 2001;Murphy et al 200la). These studies have demonstrated that rodents share a unique common ancestor, that they are composed of three major clades of mouse-like, squirrel-like, and guinea-pig-like animals, and that their closest extant relatives are lagomorphs, followed by primates, flying lemurs, and tree shrews.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological approaches have been frustrated by convergent evolution of characters (e.g., Jaeger 1988), and the current intraorder classification is therefore largely unsatisfactory. For example, the long-standing division of rodents into Hystricomorpha, Myomorpha, and Sciuromorpha, on the basis of the insertion patterns of masseter muscles, or alternatively into Hystricognathi and Sciurognathi, on the basis of the plane of incisor insertions, have both been shown to be inadequate (Hartenberger 1985;Nedbal, Honeycutt, and Schlitter 1996;Huchon, Catzeflis, and Douzery 2000;Adkins et al 2001). However, the monophyly of most rodent families seems well established (Hartenberger 1985).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, morphological synapomorphies for rodents are mainly based on dental and cranial characters (Luckett and Hartenberger 1993) that could be the result of ecological constraints and homoplasies (e.g., Li et al 1992). Recently, the growing number of molecular markers-in combination with a broader species sampling within the order Rodentia-indeed provided weak to moderate support for rodent monophyly, both with mitochondrial (Nedbal, Honeycutt, and Schlitter 1996) and nuclear sequences Douzery 1999, 2000;Adkins et al 2001;DeBry and Sagel 2001). The combination of numerous independent nuclear markers now even led to a robust support for rodent monophyly (Murphy et al 2001a).…”
Section: Introductionmentioning
confidence: 99%